Prevalencia y características clínico- epidemiológicas de neuropatía periférica en pacientes con infección por Virus de Inmunodeficiencia Humana (VIH). - Vidal Viera, Anny Estéfany (2020)
Objective: Determine the prevalence and clinical- epidemiological characteristics of peripheral neuropathy in patients with HIV infection. Method: Transversal descriptive study in patients from infectology office of the Hospital Belén de Trujillo. HIV-positive patients from 18 years old to over were included and who agreed to participate. Patients with other pathologies/conditions associated with PN and pregnancy were excluded. The Brief Peripheral Neuropathy Screening Tool was used for define PN of Distal Symmetric Polyneuropathy type. Results: The patients with PN were 43 (34.4% of 125 that formed the sample), these had mean age of 40.67 years, 31 (72.1%) were male, 23 (53.3%) were heterosexuals, 36 (83.7%) did not have exposure to D- drugs, 09 (20.9%) had tuberculosis (previous/active), mean count of 431.35 LT CD4+/mm3 and 67.4% had AIDS. The symptom more frequents were pain (55.8%) and the sign, absent/hypoactive ankle reflex (88.4%). Conclusions: The prevalence of PN in patients with HIV was high. Most patients with PN had age ≥ 40 años, were male, reported heterosexual gender, did not have exposure to D-drugs, presented tuberculosis as a more frequent opportunistic infection, had a count of LT CD4+ of 200 to 499 cells/mm3 and AIDS. The most frequent symptom was pain and the sign, absent/hypoactive ankle reflex.